Why is Europe lagging on next generation access networks? - Wolfgang Briglauer; Carlo Cambini; Michał Grajek (Bruegel, 2015)
Fibre-based next generation access (NGA) roll-out across the European Union is one of the goals of the European Commission's Digital Agenda strategy. By enabling entirely new broadband services, NGA networks have the potential to trigger productivity gains on a massive scale. There remains considerable uncertainty, however, about how the roll-out goal can best be achieved. The underlying differences between the economics of copper-based and new fibre-based broadband infrastructures should lead to a revision of the regulatory framework for telecommunications markets. While the current regulatory measures have been useful in the past decade to sustain competition and facilitate entry into a market with already-existing infrastructures, the need to create new, much faster broadband networks calls for a rethink of the scope and strictness of regulation.
Keywords: 330